Determinants of political trust during the early months of the COVID-19 pandemic: Putting policy performance into evidence - Belchior, A. M. (2021)
Basing on the previous and early months of the Covid-19 pandemic, this article analysis the main determinants of citizens’ trust in the prime minister over this period. Prior research on the political effects of the pandemic has mostly focused on identifying a rally around the flag effect, and little is known about other reasons behind the increase in trust after the outbreak of the pandemic. Based on survey data from February to July 2020 for Spanish citizens, we argue that the reasons for the increased trust in the prime minister after the pandemic outbreak are due more to performance evaluations than to emotional-related factors regarding Covid-19 health issues. We also argue that among performance evaluations, the assessment of policy performance in fighting the Covid-19 crisis is of preeminent relevance in explaining trust in the prime minister during the pandemic period. Findings widely support our argument. By comparing the effects of conventional to emotional-related factors we extend scholarship on political trust in the context of an exogenous crisis.